Semaglutide-Induced Weight Loss: Consequences for Muscle Mass and Functional Outcomes - Reizer, Barbara; Botto, Zofia; Krystek, Klaudia; Felisiak, Patrycja; Kowalczyk, Dominika; Śliwa, Zofia; Ślazyk, Dominik Andrzej (Journal of Education, Health and Sport, 2026)
Introduction: Semaglutide (Ozempic) is a long-acting GLP-1 receptor agonist used in the treatment of type 2 diabetes and obesity. Its potent effects on appetite suppression, delayed gastric emptying, and weight reduction are well documented. Increasing scientific attention has focused on its potential influence on lean body mass and skeletal muscle, as emerging evidence suggests that semaglutide-induced weight loss may include clinically relevant reductions in muscle mass. Understanding the extent and significance of these changes is essential for safe long-term therapy. Material and Methods of Research: A literature review was conducted using PubMed, Google Scholar, and Scopus. Clinical trials, observational studies, meta-analyses, and relevant preclinical research published in English between 2018 and 2024 were analyzed. Results:Evidence indicates that semaglutide-induced weight loss consistently leads to reductions in lean mass, typically comprising 20–40% of total weight lost. Mechanisms include caloric deficit, reduced protein intake, appetite suppression, and changes in anabolic signalin. Several studies demonstrated preserved muscle strength or stabilization of lean mass when therapy was combined with adequate protein intake and resistance training. Preclinical findings suggest that part of the lean mass reduction is reversible after treatment discontinuation. Conclusion: Semaglutide affects muscle mass primarily indirectly through appetite suppression and significant weight reduction. While lean mass loss is common, functional muscle decline is not inevitable and may be mitigated through dietary optimization and structured physical activity. Regular monitoring of body composition should be considered during semaglutide therapy.